PERGESERAN BUDAYA HUKUM TERHADAP PERLINDUNGAN HUKUM DALAM PROGRAM JAMINAN KEHILANGAN PEKERJAAN - Lee Sang Mok (The Juris, 2026)
This research examines the shift in legal culture among workers in Indonesia as a result of the implementation of the Job Loss Insurance Program (JKP) under Government Regulation Number 37 of 2021. Applying Lawrence M. Friedman's legal system theory encompassing three components of legal substance, legal structure, and legal culture, this study quantitatively analyzes changes in workers' legal behavior by comparing data before and after the JKP implementation. Data reveals that the JKP claim ratio against total layoff cases increased dramatically from 40.85% in 2022 (first year of implementation) to 84.20% in 2023, and 89.83% in the January-May 2024 period. The number of active JKP participants grew from 12.56 million (2022) to 16.47 million (April 2025). Benefits paid surged from IDR 44.38 billion (2022) to IDR 366.58 billion (2023). These empirical data reflect a significant shift from passive and paternalistic legal culture toward an active, rights-aware, and participatory legal culture among Indonesian workers. The study concludes that the JKP program has succeeded in driving external legal culture transformation, although implementation gaps remain, particularly regarding structural barriers for fixed-term contract workers and informal sector workers.